2012
DOI: 10.1108/01425451311287862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of managerial communication styles on employees’ attitudes and behaviours

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 45 publications
(65 reference statements)
3
42
1
Order By: Relevance
“…Effective communication is a major part of supervisor's/mentor's strategy that results in communication satisfaction (Madlock & Lightsey, 2010). Dasgupta, Suar, and Singh (2013) revealed that perceived supervisory support at the workplace leads to better communication satisfaction. The basic aim of mentoring is to build the proficiency of the mentee to the level of self-reliance, which spreads the communication of ideas across the organisation.…”
Section: Mediation Hypothesesmentioning
confidence: 99%
“…Effective communication is a major part of supervisor's/mentor's strategy that results in communication satisfaction (Madlock & Lightsey, 2010). Dasgupta, Suar, and Singh (2013) revealed that perceived supervisory support at the workplace leads to better communication satisfaction. The basic aim of mentoring is to build the proficiency of the mentee to the level of self-reliance, which spreads the communication of ideas across the organisation.…”
Section: Mediation Hypothesesmentioning
confidence: 99%
“…It is worthwhile to explore the influence of motivational orientation and communication style of unit managers and supervisors (Andersen, 2009;Dasgupta et al, 2013) on the variables that this study investigated.…”
Section: Future Researchmentioning
confidence: 99%
“…Saks (2006) posits that the two main components of SOCSUP come from perceived organisational (Kurtessis et al, 2015) and SS (Griffin, 2015;Johnson, 2015) in congruence with Kahn's (1990Kahn's ( ,1992 safety dimension -the amount of care and support provided by the organisation and supervisor. Blau's (1964) social exchange theory is considered as the most influential theoretical paradigm for understanding workplace behaviours (Dasgupta et al, 2012). Social exchange theory is based on a central foundation that the exchange of social and material resources is a primary form of human interaction.…”
Section: Social Support and Employee Engagement 2221 Social Supportmentioning
confidence: 99%
“…An efficient COMM strategy helps them communicate organisational values, such as caring for employees and regarding their opinions as important. Managers can create an environment through COMM where employees feel happier, more passionate about their jobs, exhibit attitudes and behaviours necessary for improved organisational performance (Dasgupta et al, 2012).…”
Section: Communicationmentioning
confidence: 99%